KEWENANGAN MAHKAMAH KONSTITUSI DALAM MELAKUKAN JUDICIAL REVIEW TERHADAP UNDANG-UNDANG RATIFIKASI PERJANJIAN INTERNASIONAL - Galuh Candra Purnamasari (Universitas Kristen Satya Wacana, 2017)
This paper examines Constitutional Court’s authority to review ratification acts according to UUD 1945. The problems of Constitutional Court’s authority to review ratification acts could be analyzed in Constitutional Court’s decisions on Ratification of ASEAN Charter. Although Constitutional Court has authority to review the ratification acts as seen in Constitutional Court’s decisions, there is no clear rules in Constitution which regulates any legal position and legal form of ratification acts and international treaties. The lack of clarity in the rules may cause problems concerning on the clarity of the Constitutional Court’s authority to review ratification acts in future. This paper is a literature research and it aims to find that the Constitutional Court has the authority to review ratification acts according to UUD 1945, but it does not have authority to review the substance and content of international treaties which are contained in the annex of ratification acts. The authority to review ratification acts is limited in determining the constitutionality of ratification of an international agreement through the ratification acts.